2016
DOI: 10.1038/ncomms12937
|View full text |Cite
|
Sign up to set email alerts
|

Stille coupling via C–N bond cleavage

Abstract: Cross-coupling is a fundamental reaction in the synthesis of functional molecules, and has been widely applied, for example, to phenols, anilines, alcohols, amines and their derivatives. Here we report the Ni-catalysed Stille cross-coupling reaction of quaternary ammonium salts via C–N bond cleavage. Aryl/alkyl-trimethylammonium salts [Ar/R–NMe3]+ react smoothly with arylstannanes in 1:1 molar ratio in the presence of a catalytic amount of commercially available Ni(cod)2 and imidazole ligand together with 3.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
56
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 69 publications
2
56
0
1
Order By: Relevance
“…In line with our expectations,t he nature of the ligand proved to be critical. [16] As shown in Scheme 3, our stannylation method turned out to be widely applicable regardless of the electronic and steric environments on the aryl ring. Although 2a could serve as as acrificial reducing agent, lower results were found when using Ni II precatalysts,s uggesting that cod might be stabilizing the transient metal species within the catalytic cycle.…”
mentioning
confidence: 95%
“…In line with our expectations,t he nature of the ligand proved to be critical. [16] As shown in Scheme 3, our stannylation method turned out to be widely applicable regardless of the electronic and steric environments on the aryl ring. Although 2a could serve as as acrificial reducing agent, lower results were found when using Ni II precatalysts,s uggesting that cod might be stabilizing the transient metal species within the catalytic cycle.…”
mentioning
confidence: 95%
“…Csákÿ reported the Rh(I)‐catalyzed cross coupling of (indolylmethyl)trimethylammonium iodide with aryl boronic acids . In addition, benzyltrimethylammonium salts have been exploited in Ni‐catalyzed coupling reactions with, not only aryl boronic acids, but aryl stannanes, carbon dioxides, and diboronates as well. We report herein the Ni‐catalyzed benzylation of C−H bonds in aromatic amides with benzyltrimethylammonium salts.…”
Section: Methodsmentioning
confidence: 99%
“…Since the pioneering work by Wenkert et al. in 1988, several protocols for Ni or Pd‐catalyzed cross‐coupling reactions of ammonium salts via C−N bond cleavage have been reported . We recently reported Stille (Sn) and Murahashi (Li) couplings via C−N bond cleavage.…”
Section: Methodsmentioning
confidence: 99%
“…Sincet he pioneering work by Wenkert et al in 1988, [10a] several protocols for Ni or Pd-catalyzed cross-coupling reactions of ammonium salts via CÀNb ond cleavage have been reported. [10][11][12][13][14][15][16] We recently reported Stille (Sn) [13] and Murahashi (Li) [14] couplings via CÀN bond cleavage. Wes ubsequently found that aryl aluminum reagents could react efficientlywith aryl ammoniums in the presence of aN ic atalyst.…”
mentioning
confidence: 99%